FGA Controls VEGFA Secretion to Promote Angiogenesis by Activating the VEGFR2-FAK Signalling Pathway - Li, Hui; Cai, E.; Cheng, Hongyan; Ye, Xue; Ma, Ruiqiong; Zhu, Honglan; Chang, Xiaohong (Frontiers in Endocrinology, 2022)
Background Our previous work revealed the high expression of fibrinogen alpha chain (FGA) in patients with endometriosis (EM) and that it could promote the migration and invasion of endometrial stromal cells. Angiogenesis is the key condition for the development of EM. This study was aimed to elucidate the role of FGA in endometrial stromal cells involved in angiogenesis in EM. Methods Immunohistochemistry was used to detect the microvessel density (MVD) and VEGF expression in the eutopic endometrium samples from EM and non-EM. The conditioned medium (CM) of human primary eutopic endometrial stromal cells (EuESC) and immortalized endometrial stromal cell line hEM15A with FGA knockdown were collected and used to treat human umbilical vein endothelial cells (HUVECs). Then, tube formation assay, EdU assay, wound assay, transwell assay and flow cytometry assays were performed to assess the function of HUEVCs in vitro. The angiogenic capability of HUVECs was further measured using a matrigel plug assay with BALB/c nude mice in vivo. Immunofluorescence was used to detect the expression of F-actin and VE-cadherin. RT-PCR and western blotting were used to detect the expression of angiogenesis-related factors in endometrial stromal cells and downstream signalling pathways in HUVECs. Results MVD and VEGF expression in the eutopic endometrium of EM patients were significantly higher than those in the normal endometrium of non-EM patients, and the increased MVD in EM indicates an increased risk of recurrence. Functionally, we found that CM of endometrial stromal cells with FGA knockdown could inhibit HUEVCs migration and tube formation in vitro and in vivo, while having no significant effect on HUVECs proliferation, apoptosis and cell cycle. Mechanically, the expression of VEGFA, PDGF, FGF-B, VEGF, MMP-2 and MMP-9 was reduced in hEM15A cells with FGA knockdown. CM of hEM15A cells with FGA knockdown reduced the number of microfilaments and pseudopodia, as well as the expression of VE-cadherin, and inhibited the activity of VEGFR2 and the FAK signalling pathway in HUVECs. Conclusion Our study demonstrated FGA could enhance the interaction between endometrial stromal cells and HUVECs via the potential VEGA-VEGFR-FAK signalling axis and promote EM angiogenesis, revealing a promising therapeutic approach for EM.